Going Back with Glee: A Case Study of Indonesian Migrant Workers Engaging in Circular Migration - Erna Setijaningrum; Asiyah Kassim; Rochyati Triana; Reza Dzulfikri (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
Driven by a wide range of social and cultural forces, circular migration has become a prominent phenomenon in the contemporary world, and it is especially common among Indonesian migrant workers. The research delved into what pushes Indonesian migrant workers to going back to host countries for employment after returning to their home country. A case study approach was employed by which a total of 24 semi-structured interviews were conducted with Indonesian migrant workers from Blitar, Malang, Ponorogo, and Tulungagung in East Java, Indonesia. The research reveals that non-monetary incentives such as supportive and amicable workplace environments, including the possibility of career advancements and adequate accommodations, as well as productive and family-oriented communities, act as important motivators for Indonesian migrant workers to go back to host countries. Furthermore, the research adds to the widening topography of migration studies by which it provides a broader picture in painting the “human” rationality behind circular migration in Global South.